Perception of falsified and counterfeit medicines among adults living in Mexico City and the metropolitan area: an underappreciated health risk - Celaya Pérez, Jessica Citlalli; Larios, Tania Ibargüengoitia; Fernández, Maria de los Angeles Frías; Gómez Martínez, Manuel Abraham; Carrasco, Kenneth Rubio; Villegas, Raúl Lugo; Vergara-Castañeda, Arely (Frontiers in Pharmacology, 2025)
Falsified and counterfeit medicines represent a growing global public health concern and straddles business implications, and their proliferation has intensified worldwide. An analytical cross-sectional study was carried out to validate and assess the perception of a group of residents of Mexico City and the metropolitan area regarding the problem of falsified drugs and the risks they entail, along with the purchase of medicines at unauthorized points of sale. In addition, variables associated with buying or not buying at these points of sale were identified. The results suggest that even in a sample of mainly young adults, the potential exposition to collateral effects related to the consumption of falsified or counterfeit medicines is high. Although the participants recognized that these medicines are not safe, they are not familiar with the efforts or information of the corresponding authority to warn them of this problem. In addition, low awareness of the real implications of their nature and their possible impact on heath was identified, suggesting that the falsified and counterfeit medicines’ market is a substantial and understudied issue among the Mexican population.